New Formulation towards Healthier Meat Products: Juniperus communis L. Essential Oil as Alternative for Sodium Nitrite in Dry Fermented Sausages - Vladimir Tomović; Branislav Šojić; Jovo Savanović; Sunčica Kocić-Tanackov; Branimir Pavlić; Marija Jokanović; Vesna Đorđević; Nenad Parunović; Aleksandra Martinović; Dragan Vujadinović (Foods, 2020)
The effect of Juniperus communis L. essential oil (JEO) addition at concentrations of 0.01, 0.05 and 0.10 µL/g on pH, instrumental parameters of color, lipid oxidation (2-Thiobarbituric acid reactive substances (TBARS)), microbial growth, texture and sensory attributes of dry fermented sausages produced with different levels of fat (15 and 25%) and sodium nitrite (0, 75 and 150 mg/kg) was assessed. Reduced level of sodium nitrite (75 mg/kg) in combination with all three concentrations of JEO (0.01–0.10 µL/g) resulted in satisfying physico-chemical (color and texture) properties and improved oxidative stability (TBARS < 0.3 mg MDA/kg) of dry fermented sausages produced with 25% of fat. However, sausages produced with 0.10 µL/g of JEO had untypical flavor. No foodborne pathogens (Escherichia coli, Listeria monocytogenes, Salmonella spp. and sulfite-reducing clostridia) were detected in any sample throughout the storage period (225 days). The results of this study revealed significant antioxidative activity of JEO and consequently its high potential as effective partial replacement for sodium nitrite in dry fermented sausages.